2020
DOI: 10.1001/jamanetworkopen.2020.1023
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Lay Health Worker Intervention With Symptom Burden, Survival, Health Care Use, and Total Costs Among Medicare Enrollees With Cancer

Abstract: IMPORTANCE Undertreated patient symptoms require approaches that improve symptom burden.OBJECTIVE To determine the association of a lay health worker-led symptom screening and referral intervention with symptom burden, survival, health care use, and total costs among Medicare Advantage enrollees with a new diagnosis of solid or hematologic malignant neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 35 publications
(69 reference statements)
2
38
0
Order By: Relevance
“…7 In 3 pilot projects across the United States, we demonstrated effectiveness of this approach on improved patient experiences with care, reduced cancer symptom severity, and reduced acute care use and total costs of care. [14][15][16] Between 2013 and 2016, 2 hospital-based and 3 outpatient community-based clinics implemented this program in their cancer clinics.…”
Section: Introductionmentioning
confidence: 99%
“…7 In 3 pilot projects across the United States, we demonstrated effectiveness of this approach on improved patient experiences with care, reduced cancer symptom severity, and reduced acute care use and total costs of care. [14][15][16] Between 2013 and 2016, 2 hospital-based and 3 outpatient community-based clinics implemented this program in their cancer clinics.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention resulted in improvements in electronic health record documentation of Veteran care preferences, Veteran satisfaction, and reductions in acute care use and total healthcare costs at the end-of-life as compared to usual cancer care [ 13 ]. Although we have shown that community health worker-led proactive symptom screening among civilians in community oncology clinics is associated with lower symptom burden, less acute care use, and lower total costs of care as compared to usual care [ 25 , 27 ], the feasibility and applicability of using such approaches among Veterans remains unknown. This randomized trial will provide high-level evidence regarding the feasibility and the effect of such an approach on Veteran-reported outcomes and healthcare use.…”
Section: Discussionmentioning
confidence: 99%
“…Any score of 4 or above and/or any score that has increased by 2 points from a prior assessment will be discussed and reviewed with the oncology nurse practitioner in the clinic (LB) that same day who will conduct the appropriate clinical intervention and will document any clinical intervention in response to symptoms in the electronic health record as per usual cancer care. The cutoff scores for ESAS were pre-determined by our prior work [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, glycemic control has the largest effect on health over the lifetime (compared with systolic blood pressure, total cholesterol and high density lipoprotein levels), 28 and any reduction in HbA 1c levels are likely to be beneficial. 29 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%